An iron incorporation-induced nickel hydroxide multiphase with a 2D/3D hierarchical sheet-on-sheet structure for electrocatalytic water oxidation. Issue 68 (7th August 2019) - Hao, Pin; Zhu, Wenqian; Li, Liyi; Xin, Ying; Xie, Junfeng; Lei, Fengcai; Tian, Jian; Tang, Bo
Abstract : An Fe-incorporated Ni(OH)2 multiphase with a unique 2D/3D hierarchical sheet-on-sheet structure exhibits superior catalytic activity contributed by synergistic effects, enhanced electron transport and well-exposed active sites. Abstract : An Fe-incorporated Ni(OH)2 multiphase with a unique 2D/3D hierarchical sheet-on-sheet structure exhibits superior catalytic activity and durability for water oxidation, which is contributed by synergistic effects, enhanced electron transport and an increased number of exposed active sites.